Biochemestry for nurses - Profesor Anthikad, Jacob; Gowda, Kempa; Ramiah, MS (New Delhi : Jaypee Brother, 2008)
These book are for medical students and practising doctors and are not readily useful for nurse studens.
1. Biochemical perpective to medicine 2. Chemistry of carbohydrates 3. Chemistry of protein 4. Amino Acid 5. Chemistry of proteins and other 15 more
Incluye índice Texto en inglés
Keywords: BIOQUIMICA; QUÍMICA DE LOS CARBOHIDRATOS; AMINOACIDOS